Determine the Diagnostic Yield of Ultrasound Guided Biopsy of Prostatic Lesions, Keeping Histopathology as Reference Standard, at a Tertiary Care Hospital - Ali, Fatima Wazir; Mirza, Waseem; Hassan, Ayesha (Asian Pacific Journal of Cancer Nursing, 2025)
Objective: To determine the diagnostic yield of ultrasound guided biopsy of prostatic lesions, keeping histopathology as reference standard at a tertiary care hospital. Methods: All male patients above 55 years who were referred to the Radiology department of Aga Khan University Hospital, Karachi with ultrasound/MRI finding of prostate malignancy constituted the population. After taking informed written consent and history all patients underwent transrectal ultrasound. Prostate was visualized using a transrectal biplanar ultrasound probe. Subsequently, 12 core biopsies were performed by an interventional radiologist with minimum 5 years of experience and diagnostic yield of ultrasound guided biopsy of prostatic lesions was checked keeping histopathology as reference standard. Result: Total of 116 patients with ultrasound/ MRI finding of prostatic malignancy who underwent ultrasound guided prostatic biopsy constituted the population. The mean age was 67.732+7.907 years. The diagnostic yield of ultrasound guided biopsy of prostatic lesions was 70.7%, keeping histopathology as reference standard. Conclusion: The diagnostic yield of ultrasound guided biopsy of prostatic lesions was significantly high, keeping histopathology as reference standard. The diagnostic yield increases with the increase in age and BMI.